Nevus lipomatosus of the scalp mimicking sebaceous nevus. Report of an unusual case. - Al-Oudah, N.; Al Rujaii, A.; Al-Rikabi, A.C. (European Journal of Pediatric Dermatology, 2009)
Nevus lipomatosus superficialis is an uncommon skin condition which can present as skin papules, nodules or wrinkled skin covered lesions which are either slightly pigmented or pale yellow in color. The lesions may have a vague linear distribution and are usually seen on the buttock, upper thigh or lower back. Other sites are exceptionally rare although lipomatous nevus has been described in the generalized folded skin syndrome or Michelin-Tire Baby (1, 5, 8). We report an unusual case of nevus lipomatosus superficialis which occurred on the scalp. This unreported site in addition to the clinical appearances of the lesion led to an initial diagnosis of sebaceous nevus. The clinicopathological features of nevus lipomatosus are described together with a review of its pathogenesis and a literature review of other reported unusual lipomatous nevi occurring at various sites.